2000
DOI: 10.3168/jds.s0022-0302(00)75194-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Effects of Feed Protein Reduction and Methionine on Nitrogen Use by Cows and Nitrogen Emission from Slurry

Abstract: The effects on N use and N volatilization from slurry were investigated in 24 early-lactation Brown Swiss cows (32 kg/d milk) fed four diets with 128, 124, 147 and 175 g/kg DM of crude protein (CP). All diets were supplemented with 0.75 g/kg of rumen-protected Met except for one of the low-protein rations (128 g/kg of CP). The unsupplemented low-protein ration was calculated to be deficient in Met by approximately 20%. No significant treatment effects on performance, water intake and excretion, and slurry quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
39
6
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 18 publications
16
39
6
1
Order By: Relevance
“…Consequently, a low N content of grass, as was analysed in experiment I, is fully sufficient for efficient suckler beef production and any N fertilisation will increase N emission potential. Even in dairy cows a low-protein grass seems to be sufficient as is also suggested [23] by the similar fibre digestibility in both experiments.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Consequently, a low N content of grass, as was analysed in experiment I, is fully sufficient for efficient suckler beef production and any N fertilisation will increase N emission potential. Even in dairy cows a low-protein grass seems to be sufficient as is also suggested [23] by the similar fibre digestibility in both experiments.…”
Section: Discussionsupporting
confidence: 75%
“…Excessive N is completely excreted, mainly in the form of urine N, thus clearly increasing potential ammonia emissions during storage and application of manure. Accordingly, Kröber et al [23] found a 3.5-fold increase in gaseous N loss from dairy manure when dietary crude protein content of a forage-concentrate diet (1:1) was increased from 125 to 175 g . kg -1 DN, values similar to the herbage types used in experiments I and II.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary N is converted to NH 4 much more easily in the slurry than in faecal N, and thus subject to rapid emission (e.g. Van Horn et al, 1996;Krö ber et al, 2000) either as ammonia or nitrous oxide volatilisation or nitrate leaching (Jarvis, 1993). This relationship between urinary N, total NH 4 -N in slurry DM before storage and N losses from slurry during storage was also obvious from the present results (significant at the lower slurry storage temperature).…”
Section: --supporting
confidence: 70%
“…Dairy cow diets are often limited in metabolically available protein rather than in net energy. This may open an important field of application for plant extracts containing secondary plant constituents, either to prevent a protein deficiency thus improving performance or to reduce losses of non-utilized N from the animal and from manure in the form of environmentally hazardous ammonia emissions (Kröber et al, 2000). The latter effects are particularly expected from saponins and tannins, as saponins massively reduce ruminal ammonia formation (discussed in detail by Śliwiński et al, 2002b) and tannins are known to form complexes with protein (Brooker et al, 2002).…”
Section: Introductionmentioning
confidence: 99%